2017
DOI: 10.1093/eurheartj/ehx118
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric dimethylarginine, high-density lipoproteins and cardiovascular disease

Abstract: The data identify SDMA as a marker of HDL dysfunction. These findings highlight on the pivotal role of SDMA accumulation in HDL as a mediator of pre-mature cardiovascular disease in patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 38 publications
1
57
2
4
Order By: Relevance
“…52 HDL with low SDMA is also associated with lower mortality, which may allow SDMA to be an indicator of biologically effective HDL in CKD patients. 52 It is not clear what causes the change in HDL structure and function, whether it be uremia, accumulation of other compounds, RRT, or other factors.…”
Section: Cholesterolmentioning
confidence: 98%
See 2 more Smart Citations
“…52 HDL with low SDMA is also associated with lower mortality, which may allow SDMA to be an indicator of biologically effective HDL in CKD patients. 52 It is not clear what causes the change in HDL structure and function, whether it be uremia, accumulation of other compounds, RRT, or other factors.…”
Section: Cholesterolmentioning
confidence: 98%
“…Compared to healthy controls, HDL from ESRD‐HD patients has been shown to be much less effective in cholesterol efflux and regulation of inflammation . High‐density Lipoprotein (HDL) from HD patients also promotes endothelial dysfunction via accumulation of symmetric dimethylarginine (SDMA), which is associated with increased all‐cause and cardiovascular mortality . HDL with low SDMA is also associated with lower mortality, which may allow SDMA to be an indicator of biologically effective HDL in CKD patients .…”
Section: Cardiovascular Changes In Uremic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that HDL function and composition are found to be altered in the presence of overt cardiovascular disease. As such, the presence of CAD, MI [82], heart failure [83], and stroke [84] have been associated with impaired HDL anti-atherogenic properties (i.e., stimulation of vascular NO production, anti-oxidative and anti-apoptotic potential, and cholesterol efflux capacity) [43,85]. In addition, we cannot forget that clinical trials (particularly phase III) include elderly patients under multiple drug treatments.…”
Section: Impact Of Cardiovascular Risk Factor and Co-morbidities On Hmentioning
confidence: 99%
“…Vice versa, in a preclinical hypercholesterolemia model the reduction of ADMA levels was related to less atherosclerotic lesions [67]. Interestingly, in a study including 3.310 patients undergoing coronary angiography, SDMA was identified as marker of high density lipoprotein (HDL) dysfunction, markedly in patients with renal insufficiency which may implicate another pathophysiologic link between renal disease, SDMA and premature vascular disorders [68]. In the original study by Yoo et al [24] ADMA was moreover found to be positively correlated with homocyst(e)ine.…”
Section: Adma and Sdma In Relation To Vascular Risk Factorsmentioning
confidence: 99%